PENGARUH KOMPONEN HUMAN CAPITAL TERHADAP DISIPLIN KERJA KARYAWAN DI RUMAH SAKIT BEDAH SURABAYA - Amanda Aurellia (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2021)
Surabaya Surgical Hospital has quality indicators on personnel affairs to maintain the quality of employees in providing services. One indicator is the number of delays and the fast return of structural officials. The average number of structural official delays in 2017 reached 74.94% of the predetermined standard of 0%. The indicator is used as a benchmark for assessing employee work discipline. This study was conducted to analyze the effect of human capital components consisting of individual motivation and organizational climate on employee work discipline at Surabaya Surgical Hospital. This research was an observational analytic study with cross sectional study design. Data analysis used in this study is Logistic Regression. The results of statistical test of individual motivation on work discipline show an influence, with a p value of 0.019 (smaller than α = 0.05). Statistical test results of influence organizational climate on work discipline showed an influence, namely with a p value of 0.046 (smaller than α = 0.05). The conclusion of this study is individual motivation and organizational climate have an influence on employee work discipline. It is necessary to increase employee motivation and change in the organizational climate at Surabaya Surgical Hospital with the implementation of a system reward for employees who obey the rules and give punishment to employees who violate.